2007
DOI: 10.1063/1.2818026
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of fast ions generated from laser-produced Sn plasma for extreme ultraviolet light source by H2 gas

Abstract: One of the serious problems in the laser-produced plasma for an extreme ultraviolet (EUV) light source used for the next generation lithography is the generation of fast ions that damage the EUV collector optics. In this study, the mitigation of fast ions from a laser-produced Sn plasma by a H2 background gas was investigated. It has been confirmed that H2 buffer gas at a pressure of 13.3Pa has little influence on the transmission of 13.5nm light with an optical path length of 200mm. The sputtering of a dummy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Therefore, mitigation of the debris is of importance for the development of a practical EUV lithography system. Although several methods have been developed for the debris mitigation [5][6][7], the fundamental and general approach is the use of a minimum amount of Sn that can still provide a sufficient EUV power. This type of Sn target is called a mass-limited or a minimum-mass target [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mitigation of the debris is of importance for the development of a practical EUV lithography system. Although several methods have been developed for the debris mitigation [5][6][7], the fundamental and general approach is the use of a minimum amount of Sn that can still provide a sufficient EUV power. This type of Sn target is called a mass-limited or a minimum-mass target [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a mitigation of the debris is of importance for the development of a practical EUV lithography system. Although several methods have been developed for the debris mitigation, including a magnetic field trap of ions [7], foil trap [8], and so on [9], it is difficult to mitigate the neutral particle debris because they can not be controlled by electromagnetic field. In the previous study, it was found that the neutral atoms are originated from the low-intensity part of the laser spot and the deep layer from the target surface [10] and large size debris must be also generated from the same parts.…”
Section: Introductionmentioning
confidence: 99%
“…9 In order to protect the source optics from the plasma debris, various approaches for the debris mitigation are being developed. These are deflection of the ion and plasma fluxes with a strong magnetic field, [15][16][17] stopping of these corpuscular fluxes with a background gas, 18,19 and combination of the two approaches. 9,20 The application of the background gas is important because it also allows us to mitigate the neutral atom flux (if such is present).…”
mentioning
confidence: 99%
“…20 The interaction of Sn plasma plume with background gases has been studied in various experimental conditions. [18][19][20][21][22] However, direct measurements of Sn ion stopping in the above-mentioned gases are still lacking. This paper reports on the experimental studies of Sn þ and Sn 2þ ion stopping by hydrogen for ion energies in the range of $0.1-10 keV.…”
mentioning
confidence: 99%